Hydrothermal Synthesis, Crystal Structure, and Magnetism of Na2[Ir(OH)6] and its Dehydration to Na2IrO3. Issue 6 (2nd February 2021) - Albrecht, Ralf; Poddig, Hagen; Hunger, Jens; Ruck, Michael; Benrath, Philipp; Möller, Angela; Doert, Thomas
Abstract: Yellow single‐crystals of Na2 [Ir(OH)6 ] were obtained by hydrothermal synthesis in 20 m sodium hydroxide solution at 473 K within 5 hours. X‐ray diffraction on a single‐crystal revealed the trigonal space group R 3 ‾ (no. 148) with lattice parameters a =582.76(3) pm and c =1399.30(8) pm at 100(1) K. Na2 [Ir(OH)6 ] crystallizes in a hettotype of Mg(OH)2 (brucite) and is isostructural to Na2 [Sn(OH)6 ]. The oxygen atoms are arranged in a hexagonal close packing, Na + and Ir 4+ ions occupy the octahedral voids in every second layer in an ordered manner, the voids of the next layers remain empty. The hydroxidometalate layer can be seen as isolated [Ir(OH)6 ] 2− octahedra, which are embedded in a honeycomb net of alkali metal cations. Temperature‐dependent magnetic measurements revealed paramagnetic behavior with an effective moment of 1.9 μB per iridium ion. The thermal decomposition of Na2 [Ir(OH)6 ] in air starts at about 220 °C and results in pure Na2 IrO3. Abstract :